Classic lobular carcinoma in situ and atypical lobular hyperplasia at percutaneous breast core biopsy. Issue 5 (6th November 2012) - Murray, Melissa P.; Luedtke, Chad; Liberman, Laura; Nehhozina, Tatjana; Akram, Muzaffar; Brogi, Edi
Abstract BACKGROUND: No consensus exists on the need to excise breast lesions that yield classic lobular carcinoma in situ (LCIS) or atypical lobular hyperplasia (ALH) (known together as classic lobular neoplasia [LN]) as the highest risk lesion at percutaneous core‐needle biopsy (CNB). Here, the authors report findings from 72 consecutive lesions with LN at CNB and prospective surgical excision (EXB). METHODS: Lesions that yielded LN at CNB at the authors' center have been referred for EXB since June 2004, regardless of imaging‐histologic concordance. A lesion was "concordant" if histologic findings provided sufficient explanation for imaging. An upgrade consisted of ductal carcinoma in situ and/or invasive carcinoma at EXB. Statistical analysis, including 95% confidence intervals (CIs), was performed. RESULTS: Between June 2004 and May 2009, CNB of 85 consecutive lesions yielded LN without other high‐risk histologies. Eighty of 85 lesions (94%) underwent prospective EXB. Seventy‐two of 85 lesions (90%; 42 LCIS, 30 ALH) had concordant imaging‐histologic findings. EXB yielded low‐grade carcinoma in 2 of 72 cases (3%; 95% CI, 0%‐9%). In both patients, stereotactic, 11‐gauge, vacuum‐assisted biopsy of calcifications yielded calcifications in benign parenchyma and ALH. CNB results were discordant in 8 of 80 lesions (10%; 4 LCIS, 4 ALH), and EXB yielded cancer in 3 of those 8 lesions (38%; 95% CI, 9%‐76%). The upgrade rate was significantly higher for discordant lesions versus concordant lesions (38% vs 3%; P < .01). CONCLUSIONS: Prospective excision of LN identified carcinoma in 3% (95% CI, 0%‐9%) of concordant cases versus 38% (95% CI, 9%‐76%) of discordant cases. The current data provide an unbiased assessment of the upgrade rate of LN diagnosed at CNB. Cancer 2013. © 2012 American Cancer Society.